Research Progress in the Treatment of Post-Stroke Aphasia with Theta Burst Stimulation Based on Different Stimulation Targets in the Cerebral Cortex - FANG Qun; DAI Yanhong; WANG Hong; CHEN Zhuoming; GOU Lei (康复学报)
Theta burst stimulation (TBS), as a novel non-invasive brain stimulation technique, has potential clinical significance for the recovery of speech function in patients with post-stroke aphasia (PSA) by modulating the excitability of the cerebral cortex. This study introduces the characteristics, common parameters, and safety of TBS, and provides an overview of treatment strategies for TBS applied to brain regions such as the inferior frontal gyrus, primary motor cortex, Wernicke's area, and the dorsolateral prefrontal cortex. It explores the potential effects of different stimulation targets on improving language function and the mechanisms by which TBS treatment promotes the recovery of PSA, aiming to provide a reference for the application of TBS in the clinical treatment and scientific research of PSA patients.